Gliclazide reduced oxidative stress, inflammation, and bone loss in an experimental periodontal disease model - Aurigena Antunes de ARAÚJO; Helicarlos Batista de MORAIS; Caroline Adisson Carvalho Xavier de MEDEIROS; Gerly Anne de Castro BRITO; Paulo Marcos Matta GUEDES; Sarah HIYARI; Flávia Q. PIRIH; Raimundo Fernandes de ARAÚJO JÚNIOR (University of São Paulo, 2019)
Abstract Objective The aim of this study was to evaluate the effects of gliclazide on oxidative stress, inflammation, and bone loss in an experimental periodontal disease model. Material and Methods Male albino Wistar rats were divided into no ligature, ligature, and ligature with 1, 5, and 10 mg/kg gliclazide groups. Maxillae were fixed and scanned using micro-computed tomography to quantify linear and bone volume/tissue volume (BV/TV) and volumetric bone loss. Histopathological, immunohistochemical and immunofluorescence analyses were conducted to examine matrix metalloproteinase-2 (MMP-2), cyclooxygenase 2 (COX-2), cathepsin K, members of the receptor activator of the nuclear factor kappa-Β ligand (RANKL), receptor activator of nuclear factor kappa-Β (RANK), osteoprotegerin (OPG) pathway, macrophage migration inhibitory factor (MIF), superoxide dismutase-1 (SOD-1), glutathione peroxidase-1 (GPx-1), NFKB p 50 (Cytoplasm), NFKB p50 NLS (nuclear localization signal), PI3 kinase and AKT staining. Myeloperoxidase activity, malondialdehyde and glutathione levels, while interleukin-1 beta (IL-1β) and tumor necrosis factor-alpha (TNF-α) levels were evaluated by spectroscopic ultraviolet-visible analysis. A quantitative reverse transcription polymerase chain reaction was used to quantify the gene expression of the nuclear factor kappa B p50 subunit (NF-κB p50), phosphoinositide 3-kinase (PI3k), protein kinase B (AKT), and F4/80. Results Micro-computed tomography showed that the 1 mg/kg gliclazide treatment reduced linear bone loss compared to the ligature, 5 mg/kg gliclazide, and 10 mg/kg gliclazide treatments. All concentrations of gliclazide increased bone volume/tissue volume (BV/TV) compared to the ligature group. Treatment with 1 mg/kg gliclazide reduced myeloperoxidase activity, malondialdehyde, IL-1β, and TNF-α levels (p≤0.05), and resulted in weak staining for COX-2, cathepsin k, MMP-2, RANK, RANKL, SOD-1, GPx-1,MIF and PI3k. In addition, down-regulation of NF-κB p50, PI3k, AKT, and F4/80 were observed, and OPG staining was strong after the 1 mg/kg gliclazide treatment. Conclusions This treatment decreased neutrophil and macrophage migration, decreased the inflammatory response, and decreased bone loss in rats with ligature-induced periodontitis.